Disiplin dan Komitmen Organisasi terhadap Produktivitas Tim Marketing - Rutinaias Haholongan; Ana Nur Fauziyah Priani; Dinda Prima Septiani; Silvia (LPPM Akademi Manajemen Administrasi Yogyakarta, 2026)
This study aims to analyse the influence of work discipline and organisational commitment on the marketing team's productivity. The approach used is quantitative with an associative method, and data analysis is conducted using multiple linear regression. Data were collected via questionnaires with Likert-scale items and analysed using the t-test, F-test, and coefficient of determination (R2). The results show that work discipline has a positive and significant effect on the marketing team's productivity. Similarly, organisational commitment also has a positive and significant influence. Simultaneously, both variables are proven to have a significant effect on team productivity. In addition, organisational commitment has a more dominant influence compared to work discipline. The coefficient of determination value of 0.523 indicates that 52.3% of the variation in productivity can be explained by these two variables, while the remaining is influenced by other factors outside the study. Therefore, improving work discipline and organisational commitment is an important factor in enhancing the productivity of the marketing team.